ANTIBACTERIAL ACTIVITY OF Eucalyptus globulus ON URINARY TRACT CLINICAL BACTERIAL ISOLATES (FUDMA JOURNAL OF SCIENCES, 2023)
This study evaluates on antibacterial activity of Eucalyptus globulus on urinary tract clinical bacterial isolates with a view to determine antibacterial potential of E. globulus plant parts. Agar diffusion and phytochemical screening standard methods were adopted. Results showed that five phytochemicals namely: alkaloids, flavonoids, cardiac glycosides, Saponins and tannin were found in both leaf and stem bark of the plant. Antibacterial activity of E. globulus demonstrated promising activity of the leaf ethanol extract against Escherichia coli with 37mm as inhibition zone at 500mg/ml. The E. globulus stem bark ethanol extract showed no activity against Klebsiella spp at all the concentrations tested. The minimum inhibitory concentrations (MIC) of the leaf   and stem bark were all 60mg/ml against E. coli and 60mg/ml; 100mg/ml respectively against Klebsiella spp. The Minimum Bactericidal Concentration (MBC) of the leaf and stem bark ethanol extracts of the plant were 60mg/ml and 20mg/ml against E. coli respectively and 20mg/ml and 60mg/ml respectively against Klebsiella spp. The current findings support the use of E.  globulus leaf and stem bark in the folklore medicine as antibacterial agents.
Keywords: Antibacterial potential, Eucalyptus globulus, phytochemical screening, Agar diffusion, Urinary tract